Methicillin-Resistant Staphylococcus aureus Ocular Infection after Corneal Cross-Linking for Keratoconus: Potential Association with Atopic Dermatitis. (18th March 2015) - Fasciani, Romina; Agresta, Antonio; Caristia, Alice; Mosca, Luigi; Scupola, Andrea; Caporossi, Aldo
Abstract : Purpose . To report the risk of methicillin-resistant Staphylococcus aureus (MRSA) ocular infection after UVA-riboflavin corneal collagen cross-linking in a patient with atopic dermatitis. Methods . A 22-year-old man, with bilateral evolutive keratoconus and atopic dermatitis, underwent UVA-riboflavin corneal cross-linking and presented with rapidly progressive corneal abscesses and cyclitis in the treated eye five days after surgery. The patient was admitted to the hospital and treated with broad-spectrum antimicrobic therapy. Results . The patient had positive cultures for MRSA, exhibiting a strong resistance to antibiotics. Antibiotic therapy was modified and targeted accordingly. The intravitreal reaction is extinguished, but severe damage of ocular structures was unavoidable. Conclusion . Riboflavin/UVA corneal cross-linking is considered a safe procedure and is extremely effective in halting keratoconus' progression. However, this procedure is not devoid of infectious complications, due to known risk factors and/or poor patients' hygiene compliance in the postoperative period. Atopic dermatitis is a common disease among patients with keratoconus and Staphylococcus aureus colonization is commonly found in patients with atopic dermatitis. Therefore, comorbidity with atopic dermatitis should be thoroughly assessed through clinical history before surgery. A clinical evaluation within three days after surgery and the imposition of strict personal hygiene rules are strongly recommended.